UTILIZATION OF FLUE GAS AS A CARBON DIOXIDE SOURCE FROM A COAL-BURNING POWER PLANT FOR THE CULTIVATION OF MICROALGAE IN OUTDOOR CIRCULAR PONDS - SWAMINATHAN PALANISAMI; THIRUVENKADAM VISWANATHAN; NICHOLAS DUDENHOEFFER; KEESOO LEE; PAUL KI-SOUK NAM (International Journal of Pharma and Bio Sciences, 2013)
Flue gas originating from a coal-fired power plant was used as a carbon dioxide source for microalgae cultivation. Raw flue gas without scrubbing or desulfurization was diluted with compressed air in such a way as to attain 1%, 2%, and 4% CO2. Throughout the 2010, from May to October, growth response was studied. While sparging pure CO2, a proportionate increase in the biomass was observed corresponding to the increasing CO2 percentage (1%, 2%, and 4%). CO2 in the form of flue gas yielded less growth with increasing percentage; however, the lipid production revealed a steady elevation on sparging a higher percentage of flue gas. To investigate the toxic effects of flue gas entities, factors related to the stress-stabilization mechanisms were studied. Activity staining of stress stabilizing enzymes - superoxide dismutase and esterase showed increased activity. The used concentration of flue gas has not hindered the algal growth, which was evident by the organism’s active nitrogen metabolism as revealed by the increased activity of glutamine synthetase. To understand the fate of CO2 metabolism; Polyphenol oxidase activity was tested, which found decreased in activity.